Strategi Penguatan Peran Anak Muda Menghadapi Perubahan Iklim Pekalongan - Fikri Kurniali, Muhammad Haidar; Aifil Indira, M. Rakhma; Naufal Maulana, M. Dimas; Arrafa, Ahmad Fadzla (JURNAL LITBANG KOTA PEKALONGAN, 2025)
The study aims to analyze climate change and the role of youth in facing the challenges of digital technology in Pekalongan, as well as to find evidence-based solutions. The method used is qualitative research with a literature study, collecting primary and secondary data through library research and descriptive surveys. The results show that Pekalongan faces climate change issues such as land subsidence, sea level rise, flooding, and vector-borne diseases. Youth are confronted with narcotizing dysfunction and the commodification of social media. Fundamental initiatives such as carbon footprint awareness, green marketing, and avoiding greenwashing are needed. However, surveys indicate that youth understanding of carbon footprints is still low. Therefore, new methods of environmental education are necessary. Previous research shows that applications can enhance knowledge of carbon footprints and environmentally friendly lifestyles, with features like carbon footprint calculators, education, and gamification. This study recommends fundamental environmental education, avoiding social media dominance, leveraging Pekalongan's local wisdom, and emphasizing individual movements that can become collective.